PENGARUH GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA DENGAN MODERASI LOCUS OF CONTROL DAN KEJELASAN TUGAS PADA PERAN AUDITOR YUNIOR - LOSIANA LOMANTO, SILVIA (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
fairly important. Job satisfaction is seen as one of the factors that affect employee performance. Besides job satisfaction is one of the goals of the KAP. One of the factors that affect job satisfaction is leadership style. Style of leadership is an attitude of someone who can influence others. In addition, some experts argue that the Locus of Control variables may moderate the relationship between leadership style to job satisfaction. Locus of control is a way of looking someone about something that happened to him. Job satisfaction also depends on the auditor explained that the task given to him. Therefore, this study will examine the relationship between leadership style on job satisfaction junior auditors with moderation variable locus of control and clarity of the task. This study uses a questionnaire as a tool to collect data. Questionnaires distributed by sending directly to the KAP-KAP contained in Surabaya. The object of this study was a junior auditor who worked on KAP for less than two years. A total of 200 questionnaires had been distributed, and only 70 questionnaires that can be processed and carried out the research. The results of this study was jointly leadership style variable, locus of control, and task clarity affects job satisfaction, but based on statistical T-test generated that leadership style variables had no effect on job satisfaction of junior auditors, as well as the locus of control and clarity of the task is not is a variable that supports moderation between relationship leadership style and job satisfaction.